The Effect of Utilization of Sweet Potato Flour as Energy Source of Broiler Feed at Finisher Period to Carcass Weight, Chest Weight, Thigh Weight and Abdominal Fat (Faculty of Animal Science Universitas Brawijaya, 2011)
The objective of current research is was to know the effect of feeding sweet potato flour as a source of energy to carcass weight, chest weight, thigh weight, and abdominal fat.The material of the research were 80 finisher male broiler with initial weight of 963.37 Â± 31.23 g. Completely Randomized Design (CRD) used for research method which consisted of 4 treatment, namely feeding without sweet potato flour (P0), with concentration of sweet potato flour of 10% (P1), 20% (P2) and 30% (P3).The parameter of research were carcass weight, chest weight,thigh weight and abdominal fat. The results showed that the gift effect of sweet potato flour to carcass weight were P0 1199.4%; P1 1138.98%; P2 1076.6; P3 1038.2; chest weight of P0 358.08; P1 366.6; P2 337.8; and P3 323.4%; thigh weight of P0 479.8; P1 472.94; P2 468.4; and P3 442; and abdominal fat of P0 33.2; P1 35.6; P2 25.4; P3 27.8. It could be concluded that the concentration of 10% sweet potato flour from total feeding gave the best treatment. Â Keywords : sweet potato flour, carcass weight, chest weight, thigh weight, abdominal fat Â